Implementation Process and Impacts of a Participatory HIV Research Project with Key Populations. (31st May 2018) - Dias, Sónia; Gama, Ana; Simões, Daniel; Mendão, Luís
Abstract : A participatory HIV research project was conducted with sex workers (SW) and men who have sex with men (MSM) to understand epidemiological HIV dynamics and associated sociobehavioural factors among these vulnerable groups. We examine the impact of this project, critically analysing the processes undertaken and focusing on the advantages and the challenges faced. A partnership was built through two Community Advisory Boards (CABs) and a Scientific Commission (SC). Regular meetings, workshops, and focus groups were conducted with CABs, SC, and partners to assess the processes and outcomes of the project implementation. This participatory research produced change processes with impacts at different levels: individuals, community organizations, health professionals, academics, and policy-makers. Advantages of the participatory process were encountered but also challenges, evidencing the dynamic and complex nature of each project's stage. This project showed that participatory research can work as an intervention. Indeed, it triggered a dynamic and interactive process of knowledge coproduction and translation into effective community-oriented health actions and policies. The participatory research reproduced an innovative alliance for HIV prevention and sexual health promotion responsive to local needs and priorities. Further efforts are needed to systematize and evaluate the processes and impacts of participatory health research.